Psychological distress is negatively associated with ideal cardiovascular health behaviour in nationally representative school sample of adolescents in Vanuatu - Supa Pengpid (2022)
This study aimed to determine the prevalence, distribution, and correlates of ideal cardiovascular health behaviour (CVHB) among adolescents in Vanuatu. Data from the cross-sectional nationally representative school-based student health survey in Vanuatu in 2016 were analyzed that had complete CVHB measurements. The prevalence of poor (0-1 ideal metrics) CVHB was 12.4%, intermediate (2 ideal metrics) 34.1%, and ideal CVHB (3-4 ideal metrics) 53.5%. Only 6.2% had ideal CVHB (all 4 metrics), 38.2% intermediate CVH (≥1 metric in the intermediate category and none in the poor category), and 55.6% had poor CVH (≥1 metric in poor category). In adjusted logistic regression analysis, multiple psychological distress (Adjusted Odds Ratio-AOR: 0.59, 95% Confidence Interval-CI: 0.42-0.84) was negatively associated with meeting 3-4 ideal CVHB metrics. In addition, in the unadjusted analysis, male sex was negatively and school attendance and peer support were positively associated with meeting 3-4 ideal CVHB metrics. The proportion of meeting 3-4 ideal CVHB metrics was low among adolescents in Vanuatu. School-wide intervention programmes should be implemented in aiding to improve CVHB in Vanuatu.